2020
DOI: 10.1002/jcp.29962
|View full text |Cite
|
Sign up to set email alerts
|

RAB39B's role in membrane traffic, autophagy, and associated neuropathology

Abstract: Neuropathological disorders are increasingly associated with dysfunctions in neuronal membrane traffic and autophagy, with defects among members of the Rab family of small GTPases implicated. Mutations in the human Xq28 localized gene RAB39B have been associated with X-linked neurodevelopmental defects including macrocephaly, intellectual disability, autism spectrum disorder (ASD), as well as rare cases of early-onset Parkinson's disease (PD). Despite the finding that RAB39B regulates GluA2 trafficking and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 178 publications
(294 reference statements)
0
14
0
Order By: Relevance
“…Although the mechanisms by which a loss of RAB39B leads to the dyshomeostasis of aSyn is unknown, the disruption of autophagic clearance has recently been proposed as central to this, in line with the impairments seen following the expression of mutations within the RAB39B GEF C9orf72 128 and would appear to be supported by the autophagy deficits in RAB39B knockout mice. 124 Whilst such a proposition is interesting it remains unclear why such generalized failure of lysosomal clearance would preferentially lead to the accumulation and aggregation of aSyn over other aggregate prone proteins, and indeed several studies have failed to find an impact upon lysosomal degradation following the loss of RAB39B.…”
Section: Regulation Of Asyn Homeostasis Via Rab39bmentioning
confidence: 88%
“…Although the mechanisms by which a loss of RAB39B leads to the dyshomeostasis of aSyn is unknown, the disruption of autophagic clearance has recently been proposed as central to this, in line with the impairments seen following the expression of mutations within the RAB39B GEF C9orf72 128 and would appear to be supported by the autophagy deficits in RAB39B knockout mice. 124 Whilst such a proposition is interesting it remains unclear why such generalized failure of lysosomal clearance would preferentially lead to the accumulation and aggregation of aSyn over other aggregate prone proteins, and indeed several studies have failed to find an impact upon lysosomal degradation following the loss of RAB39B.…”
Section: Regulation Of Asyn Homeostasis Via Rab39bmentioning
confidence: 88%
“…C19orf53 correlates with PARK7, SOD1 and ROCK1 which have roles in autophagic proteolysis and the formation of the autophagosome [53][54][55] . Our correlation analysis also reveals C1orf109 is highly correlated with TMEM41B, ATG4C RAB39B, TRIM8, and NPRL3 which are also regulators of autophagy [56][57][58][59] . C1orf109 was shown here to be highly correlated with SNCA.…”
Section: Differential Correlation Analysis Resultsmentioning
confidence: 55%
“…More recently, additional evidence reported that loss-of-function mutations in RAB39B , including whole gene deletion, missense, splicing and frameshift variants, also led to the development of an X-linked form of rare early-onset PD associated with intellectual disability [ 72 , 73 ]. RAB39B is a neuronal protein which is localized in the Golgi compartment and acts as an essential regulator of vesicular trafficking, possibly affecting α-syn homeostasis [ 74 ]. This protein is also believed to play a role in the modulation of growth cone function, neurite morphology, synaptic plasticity and synapse formation [ 74 , 75 ].…”
Section: The Genetic Landscape Of Parkinson’s Disease: a Brief Overviewmentioning
confidence: 99%